2001
DOI: 10.1074/jbc.m102966200
|View full text |Cite
|
Sign up to set email alerts
|

Oxazolidinones Mechanism of Action: Inhibition of the First Peptide Bond Formation

Abstract: Oxazolidinones are potent inhibitors of bacterial protein biosynthesis. Previous studies have demonstrated that this new class of antimicrobial agent blocks translation by inhibiting initiation complex formation, while post-initiation translation by polysomes and poly(U)-dependent translation is not a target for these compounds. We found that oxazolidinones inhibit translation of natural mRNA templates but have no significant effect on poly(A)-dependent translation. Here we show that various oxazolidinones inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 27 publications
(25 reference statements)
1
26
0
1
Order By: Relevance
“…However, the ability of oxazolidinones to inhibit initiation complex formation has been observed only at high ratios of oxazolidinones to ribosomes. Moreover, attempts to demonstrate that oxazolidinones inhibit peptide bond formation have not produced clear results, except for the inhibition of the first peptide bond as a consequence of the interference of linezolid with the binding of initiator fMet-tRNA(i)(Met) (35). Alternative mechanisms of oxazolidinone action have been proposed when experiments showed that oxazolidinones had a significant in vivo effect on frameshifting and nonsense suppression at concentrations below the MIC (48) and were also able to inhibit 50S ribosomal subunit assembly (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of oxazolidinones to inhibit initiation complex formation has been observed only at high ratios of oxazolidinones to ribosomes. Moreover, attempts to demonstrate that oxazolidinones inhibit peptide bond formation have not produced clear results, except for the inhibition of the first peptide bond as a consequence of the interference of linezolid with the binding of initiator fMet-tRNA(i)(Met) (35). Alternative mechanisms of oxazolidinone action have been proposed when experiments showed that oxazolidinones had a significant in vivo effect on frameshifting and nonsense suppression at concentrations below the MIC (48) and were also able to inhibit 50S ribosomal subunit assembly (8).…”
Section: Discussionmentioning
confidence: 99%
“…The fragment P-site substrate CCA-Phe-X-Biotin was synthesized as described in Ref. 1 Preparation of Oxazolidinone-resistant 23 S RNA Mutant Ribosomes-Oxazolidinone-resistant mutant strains carrying a single mutated copy of ribosomal 23 S RNA were selected and characterized as reported in Refs. 2 and 33 using plasmids with site-directed mutations (10) and a recently described single plasmid-encoded rRNA operon system in Escherichia coli (11).…”
Section: Reagents and Materials-puromycin Chloramphenicol And Trna Imentioning
confidence: 99%
“…Oxazolidinones, the only novel class of antibiotics identified in the last two decades, are the focus of intensive discovery efforts (1)(2)(3)(4)(5)(6)(7)(8)(9). Linezolid, an oxazolidinone, is approved for treatment of infections caused by Gram-positive bacteria that are resistant to other antibiotics.…”
mentioning
confidence: 99%
“…Oxazolidinones inhibit bacterial protein synthesis via competitive binding to the 23S rRNA in the catalytic site of the bacterial 50S ribosomes (3,4). Linezolid (LZD), the first oxazolidinone that entered clinical use, exhibits bacteriostatic activity against M. tuberculosis with an MIC of less than 1 g/ml (5) and has been used against MDR/XDR TB cases (4,6,7). However, long-term administration of LZD may cause severe side effects such as anemia, thrombocytopenia, and peripheral neuropathy (8).…”
mentioning
confidence: 99%